Exportadores y consignatarios del café costarricense a finales del siglo XIX - Peters Solórzano, Gertrud (2004)
This article intends to study the unveiling of statues carried out during the national independence celebrations between 1876 and 1921. Its fundamental purpose is to understand how a certain political period from the past was chosen, as well as the discourse strategies used for promoting and representing it through statuary activities. Therefore, it assesses the discussions that arose in relation with the selection of historical characters that were to be sculpted as public statues, and the role played by the representatives in the preparation of an official memory.